Experimental platforms for the investigation of spatiotemporal patterns in the rhizosphere—Laboratory and field scale. Issue 1 (9th August 2020) - Vetterlein, Doris; Lippold, Eva; Schreiter, Susanne; Phalempin, Maxime; Fahrenkampf, Toni; Hochholdinger, Frank; Marcon, Caroline; Tarkka, Mika; Oburger, Eva; Ahmed, Mutez; Javaux, Mathieu; Schlüter, Steffen
Abstract: The numerous feedback loops between roots, microorganisms, soil chemical and physical properties, and environmental variables result in spatial parameter patterns which are highly dynamic in time. In order to improve our understanding of the related rhizosphere processes and their relevance at the soil–plant system scale, experimental platforms are required. Those platforms should enable (1) to relate small scale observations (nm to dm) to system behaviour, (2) the integration of physical, chemical and biological sampling approaches within the same experiment, and (3) sampling at different time points during the life cycle of the system in question. Here we describe what requirements have to be met and to what extent this has been achieved in practice by the experimental platforms which were set up within the framework of DFG priority programme 2089 "Rhizosphere Spatiotemporal Organisation—a key to rhizosphere functions". It is discussed to what extent theoretical considerations could be accommodated, in particular for the comparison across scales, i.e ., from laboratory to field scale. The latter scale is of utmost importance to overcome the trade‐off between fraction of life cycle covered and the avoidance of unrealistic root length densities.